2017
DOI: 10.1126/scitranslmed.aaf5347
|View full text |Cite
|
Sign up to set email alerts
|

A semisynthetic Streptococcus pneumoniae serotype 8 glycoconjugate vaccine

Abstract: Glycoconjugate vaccines based on capsular polysaccharides (CPSs) of pathogenic bacteria such as Streptococcus pneumoniae successfully protect from disease, but suffer from incomplete coverage, are troublesome to manufacture from isolated CPSs and lack efficacy against certain serotypes. Defined, synthetic oligosaccharides are an attractive alternative to isolated CPSs but require the identification of immunogenic and protective oligosaccharide antigens. Here, we describe a medicinal chemistry strategy based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 43 publications
2
80
0
Order By: Relevance
“…in the chemical synthesis of complex glycans including automated glycan assembly (AGA) have made the synthesis of a variety of diverse oligosaccharides resembling the CPS of different serotypes possible. Active immunization of mice and rabbits with CRM197 conjugates with ST2 (17), ST3 (18), ST5 (9), ST8 (19), and ST14 (20, 21) elicits opsonic antibodies that were shown in some cases to be protective in challenge models of disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…in the chemical synthesis of complex glycans including automated glycan assembly (AGA) have made the synthesis of a variety of diverse oligosaccharides resembling the CPS of different serotypes possible. Active immunization of mice and rabbits with CRM197 conjugates with ST2 (17), ST3 (18), ST5 (9), ST8 (19), and ST14 (20, 21) elicits opsonic antibodies that were shown in some cases to be protective in challenge models of disease.…”
mentioning
confidence: 99%
“…The medicinal chemistry approach has identified di-to tetrasaccharides as potential vaccine candidates (11). The immunogenicity of the CPS depends among other factors on rare sugars and labile functional groups (9,17,19). Stable oligosaccharide analogs can fix production problems such as those encountered for ST5 CPS due to the labile ketone present in the repeating unit (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method eases the creation of glycan microarrays, which are used to uncover immunodominant glycan epitopes (glycotopes) that can subsequently be incorporated into glycoconjugate vaccines. This strategy was first demonstrated by Schumann et al to design a vaccine that protects against S. pneumoniae serotype 8 [21]. Although prohibitive cost has generally limited AGA technology to microarray applications and prevented it from being used to synthesize sufficient quantities of carbohydrates for vaccination, further developments that streamline the process may increase its scalability [22].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic glycan antigens elicit a significantly stronger antibody response in rabbits when compared to mice. [34] Rabbits were immunized with CRM197- 1 conjugate formulated with alum, an adjuvant approved for use in humans. [35] The serological analysis using glycan microarrays and ELISA revealed that CRM197- 1 conjugate elicits a robust immune responses against native CR- Kp CPS (Supporting Information, Figure S3).…”
mentioning
confidence: 99%